2001
DOI: 10.1016/s0736-0266(01)00026-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on systemic and bone concentrations of growth factors in rats

Abstract: Exercise can prevent bone loss and increase bone density. Growth factors such as insulin-like growth factor-I (IGF-I) and transforming growth factor P (TGFB) are thought to be involved in the local response to mechanical loading, resulting in bone remodelling. We tested the effect of additional weight bearing during exercise on the systemic response of IGF-I and local bone response of IGF-I and TGFP.Thirty-four female Wistar rats (aged 3 months, weight 226.9 4~ 20.2 g) were randomly divided in four groups: gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
2
15
2
Order By: Relevance
“…It was found that the plasma IGF-1 levels did not decrease either by short bout exercise or physical training in adults [32]. In rodent models, both our studies and others found that exercise with ad libitum feeding was not sufficient to decrease plasma IGF-1 levels [7,33]. When the exercised mice were fed an iso-caloric diet as their sedentary counterpart, the plasma levels of IGF-1 were significantly reduced [7].…”
Section: Page 4 Ofmentioning
confidence: 51%
“…It was found that the plasma IGF-1 levels did not decrease either by short bout exercise or physical training in adults [32]. In rodent models, both our studies and others found that exercise with ad libitum feeding was not sufficient to decrease plasma IGF-1 levels [7,33]. When the exercised mice were fed an iso-caloric diet as their sedentary counterpart, the plasma levels of IGF-1 were significantly reduced [7].…”
Section: Page 4 Ofmentioning
confidence: 51%
“…Similarly, ML has been shown to stimulate IGF-I expression in bone cells in vivo (7,18,25). Although there is a considerable body of data in the literature to implicate a role for IGF-I in mediating the mechanical strain response in bone, direct evidence to demonstrate a cause-and-effect relationship between an increase in IGF-I expression and skeletal changes is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples (1 ml each) were taken by intracardiac puncture on day 1 and in weeks 1, 2 and 4, and stored at −20°C until analysis (Bravenboer et al, 2001). Serum TGF-β1 concentration was measured with a commercially available enzyme-linked immunosorbent assay (ELISA) (BMS608/2 m TGF-β1, Bender Med Systems, CA, USA).…”
Section: Serum Analysesmentioning
confidence: 99%